Zetorchestes krisperi sp. nov. (Acari: Oribatida: Zetorchestidae) from Vietnam, with juvenile morphology and identification key to known species of the genus - Kolesnikov, Vasiliy B.; Leonov, Vladislav D. (Zootaxa, 2021)
The description of a new species of oribatid mites (Oribatida) of the family Zetorchestidae—Zetorchestes krisperi sp. nov.—is proposed based on adult and tritonymph specimens collected from rainforest soil of Bi Dup-Nui Ba National Park (southern Vietnam). We also review the distinguishing characteristics for Zetorchestes species and present an identification key to Zetorchestes species of the world. Diagnostic features of Zetorchestes nymphs are discussed.